Relationship Between Person-Organization Fit and Teacher Burnout in Kindergarten: The Mediating Role of Job Satisfaction - Zang, Lingling; Chen, Yameng (Frontiers in Psychiatry, 2022)
As an important organizational factor, person-organization fit in kindergartens may lead to teacher burnout when it is unfitted. In order to explore the influence mechanism of person-organization fit on teacher burnout in kindergartens, this study introduced the variable of job satisfaction to study the mediating effect of job satisfaction on the relationship between person-organization fit and teacher burnout in kindergartens. A total of 637 teachers from Henan, China, were surveyed by Person-Organization Fit Scale, Job Satisfaction Scale and Maslach Burnout Inventory. Results showed that person-organization fit, job satisfaction and teacher burnout were negatively correlated. Person-organization fit is positively correlated with job satisfaction. Job satisfaction partially mediated the relationship between person-organization fit and teacher burnout in kindergartens. In the end, the results of the relationship between person-organization fit, job satisfaction, and teacher burnout in Chinese kindergartens were discussed in this study.